2021
DOI: 10.3758/s13428-020-01526-w
|View full text |Cite
|
Sign up to set email alerts
|

The Difference Spotting Task: A new nonverbal measure of cheating behavior

Abstract: To understand when, how, and why people cheat, the ability to detect cheating in a laboratory setting is crucial. However, commonly used paradigms are confronted with a conflict between allowing participants to believe they can cheat unnoticed and allowing experimenters to detect cheating. This project aimed to develop and establish a new nonverbal task to resolve this conflict. Study 1 and Study 2 developed a new unsolvable paradigm called the Difference Spotting Task. In Study 1, participants were incentiviz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
0
18
3
Order By: Relevance
“…five) represents an important, ethical limitation of our two studies. However, and as also highlighted by Liu and colleagues for a similar task [ 47 ], the alternative, truthful version of our STDT would have to rely on images that differ for a certain number of details, a proportion of which is very difficult (but not impossible) to find. While this methodology would eliminate deception on the part of researchers, it would also prevent them from recognizing participants who lie and those who do not with absolute certainty, and therefore from studying dishonest behaviours in similar settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…five) represents an important, ethical limitation of our two studies. However, and as also highlighted by Liu and colleagues for a similar task [ 47 ], the alternative, truthful version of our STDT would have to rely on images that differ for a certain number of details, a proportion of which is very difficult (but not impossible) to find. While this methodology would eliminate deception on the part of researchers, it would also prevent them from recognizing participants who lie and those who do not with absolute certainty, and therefore from studying dishonest behaviours in similar settings.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that different versions of the STDT were recently used to investigate dishonesty [ 46 , 47 ] and unveil its underlying neural correlates [ 48 ]. Crucially, this task has the advantage of being nonverbal, which allows us to investigate moral behaviours in populations differing in age and education.…”
Section: Methodsmentioning
confidence: 99%
“…The single‐player task adopted a 2 (8 s vs. 60 s time‐limit) × 2 (self or charity as beneficiaries) design. There were 60 trials covering four types of puzzles: the adding‐to‐10 matrix puzzle (Mazar et al, 2008 ; Zhong et al, 2010 ), the difference spotting puzzle (Liu et al, 2021 ; Speer et al, 2020 ), the Chinese idioms puzzle, and the logic reasoning puzzle (the control puzzle to disguise the experiment as a test of measuring problem‐solving ability). Before the experiment, participants were informed that they were participating in a problem‐solving task.…”
Section: Methodsmentioning
confidence: 99%
“…Commonly used measures to identify dishonesty at an individual level include ability tests, such as the matrix task (Mazar et al, 2008), where self-reported outcomes are compared to the actual performances, deception games, or unsolvable paradigms. In unsolvable paradigms, participants are asked to indicate whether they solved a specific task, even though the tasks are designed to be unsolvable (Liu et al, 2021). Examples such as "senderreceiver" games or "tax compliance" experiments are utilized to detect deceptive behavior in either interactive and non-interactive communication settings (Burgoon and Buller, 1994;Capraro, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Examples such as "senderreceiver" games or "tax compliance" experiments are utilized to detect deceptive behavior in either interactive and non-interactive communication settings (Burgoon and Buller, 1994;Capraro, 2018). Despite some drawbacks (see Heyman et al, 2020;Liu et al, 2021or Blume et al, 2002 for further information), these approaches allow for direct inferences about individual behavior, making them essential for accurately linking personal factors to dishonesty. One of the rarely discussed drawbacks of tasks like the matrix task is the occurrence of honest mistakes (Heyman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%